Ultrafast dynamics of fully reduced flavin in catalytic structures of thymidylate synthase ThyX. Issue 39 (4th October 2021) - Dozova, Nadia; Lacombat, Fabien; Lombard, Murielle; Hamdane, Djemel; Plaza, Pascal
Abstract : Transient absorption spectroscopy reveals the impact of substrates on the ultrafast dynamics of FADH − in flavin-dependent thymidylate synthase ThyX. Abstract : Thymidylate is a vital DNA precursor synthesized by thymidylate synthases. ThyX is a flavin-dependent thymidylate synthase found in several human pathogens and absent in humans, which makes it a potential target for antimicrobial drugs. This enzyme methylates the 2′-deoxyuridine 5′-monophosphate (dUMP) to 2′-deoxythymidine 5′-monophosphate (dTMP) using a reduced flavin adenine dinucleotide (FADH − ) as prosthetic group and (6 R )- N 5, N 10 -methylene-5, 6, 7, 8-tetrahydrofolate (CH2 THF) as a methylene donor. Recently, it was shown that ThyX-catalyzed reaction is a complex process wherein FADH − promotes both methylene transfer and reduction of the transferred methylene into a methyl group. Here, we studied the dynamic and photophysics of FADH − bound to ThyX, in several substrate-binding states (no substrate, in the presence of dUMP or folate or both) by femtosecond transient absorption spectroscopy. This methodology provides valuable information about the ground-state configuration of the isoalloxazine moiety of FADH − and the rigidity of its local environment, through spectra shape and excited-state lifetime parameters. In the absence of substrate, the environment of FADH − in ThyX is only mildly more constrained than that of free FADH − in solution. The addition of dUMP however narrows the distribution of ground-state configurations and increases the constraints on the butterfly bending motion in the excited state. Folate binding results in the selection of new ground-state configurations, presumably located at a greater distance from the conical intersection where excited-state decay occurs. When both substrates are present, the ground-state configuration appears on the contrary rather limited to a geometry close to the conical intersection, which explains the relatively fast excited-state decay (100 ps on the average), even if the environment of the isoalloxazine is densely packed. Hence, although the environment of the flavin is dramatically constrained, FADH − retains a dynamic necessary to shuttle carbon from folate to dUMP. Our study demonstrates the high sensitivity of FADH − photophysics to the constraints exerted by its immediate surroundings.